Penglibatan masyarakat tempatan dalam industri pembalakan : satu kajian kes di Medamit, Limbang - Johnny, Rasit. (Universiti Malaysia Sarawak (UNIMAS), 2001)
This study was conducted to determine the level of participation the local people of Medamit, Limbang in logging industry. The objectives of this study were determine the factors that encourage people to participate in logging industry, to the relationship between level of involvement with demographics attributes, socio economic and characteristics the respondents perception of impact of logging industry to the socio economy and environment. Self-administrative questionnaire and interview were used in the data collection. A total of 50 respondents were taken, from five longhouse in Medamit area.The data collected were then analyzed by lIsing SPSS program (Statistic Packages for the Social Sciences). The result were presented in the fonn of frequency, percentage distribution, correlation (spearman rank-order) and t-test. The finding of the study shows that the wages responsibility to the family become the motivate factor to participate in the logging industry. The impact of the logging industry include increase standard of living and environmental damage sllch as river pollution and forest destruction.